MAGED4B is a Poor Prognostic Marker of Stomach Adenocarcinoma and a Potential Therapeutic Target for Stomach Adenocarcinoma Tumorigenesis - Luo WZ; Li X; Wu XX; Shang YW; Meng DH; Chen YL; Zhang QS (International Journal of General Medicine, 2023)
Wen-Zhao Luo,1,2 Xian Li,2 Xiu-Xia Wu,2 Yi-Wan Shang,1,3 Dan-Hua Meng,1,3 Yu-Long Chen,1,3 Qin-Sheng Zhang2 1School of Basic Medicine (Zhongjing School), Henan University of Chinese Medicine, Zhengzhou, Henan Province, 45000, People’s Republic of China; 2Department of Hepatobiliary and Spleen Stomach, Henan Province Hospital of Traditional Chinese Medicine, Zhengzhou, Henan Province, 450000, People’s Republic of China; 3Academy of Chinese Medical Sciences, Henan University of Chinese Medicine, Zhengzhou, Henan Province, 45000, People’s Republic of ChinaCorrespondence: Yu-Long Chen, School of Basic Medicine (Zhongjing School), Henan University of Chinese Medicine, No. 156 East Jinshui Road, Jinshui District, Zhengzhou, Henan Province, 45000, People’s Republic of China, Email chenyulong1977@163.com Qin-Sheng Zhang, Henan Province Hospital of Traditional Chinese Medicine, Department of Hepatobiliary and Spleen Stomach, No. 6 Dongfeng Road, Jinshui District, Zhengzhou, Henan Province, 450000, People’s Republic of China, Email zhangqinsheng0319@163.comBackground: Gastric cancer is the second most common cause of cancer death worldwide with poor overall prognosis. It is important to study the molecular mechanism of stomach adenocarcinoma (STAD). MAGED4B, a member of the melanoma antigen gene (MAGE) family, is highly expressed in many tumor cells and is associated with tumor progression. Its prognostic value in and the function of the encoded protein are still unclear.Methods: The data of 415 STAD tissues was retrieved from TCGA database, and the expression level of MAGED4B mRNA was evaluated. The correlation between the expression of MAGED4B mRNA and the progression free survival (PFS) time of STAD patients was evaluated by Kaplan Meier analysis. The STAD cell lines with overexpressed and silent MAGED4B were constructed, and the effects of MAGED4B on the viability, migration and proliferation were evaluated by the CCK-8, scratch test and EDU test. The flow cytometry was used to detect apoptosis with overexpressed and silent MAGED4B under the cisplatin treatment, and WB was used to detect the expressions of related proteins, such as TNF-α.Results: The expression level of MAGED4B mRNA in the STAD tissues was higher than that in the normal tissues, and its high expression was related to poor PFS. The overexpression of MAGED4B in the STAD cell lines can promote the vitality, motility and proliferation of the STAD cells, while the silencing of MAGED4B can inhibit the above three cell functions of the STAD cells. The overexpression of MAGED4B can reduce the cisplatin induced apoptosis and increase the cisplatin IC50; the silencing of MAGED4B can promote the cisplatin induced apoptosis and reduce the cisplatin IC50. The overexpression of MAGED4B reduced the protein levels of TRIM27 and TNF- α.Conclusion: MAGED4B could be a valuable prognostic biomarker and a therapeutic target for gastric adenocarcinoma of great interest.Keywords: stomach adenocarcinoma, MAGED4B, prognosis, biomarkers